EUS-Guided Pancreatic Diagnosis and Beyond - Vignesh, Shivakumar; Hoffe, Sarah E; Saif, Muhammad Wasif (JOP. Journal of the Pancreas, 2011)
The therapeutic ability of endoscopic ultrasound has expanded, especially in assisting with radiation planning for image guided radiation techniques such as stereotactic body radiation therapy. Endoscopic ultrasound enables precise placement of fiducial markers into pancreatic cancers to accurately delineate the position of the target lesion as it moves with respiration. The authors summarize the data presented at the 2011 American Society of Clinical Oncology (ASCO) Gastrointestinal Cancers Symposium, including Abstracts #302, #327, #176, #182, and #349. Image: Dose painting of pancreas protocol CT scan (detail).